Implementation of Extreme Programming Method in Web Based Digital Report Value Information System Design - Adi Supriyatna; Diah Puspitasari (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
The process of data collection and processing of student scores that is carried out continuously from year to year is felt to be unable to produce fast, precise and accurate information, because it takes a long time. Computerized information system processing student grades is expected to be able to ease the work of homeroom teachers, so that they can produce valid information in a short time and can be accessed anywhere. With good processing and management, value data processing will be easier, faster, more accurate. The purpose of this research is to build a web-based digital report card information system as a solution offered to help solve problems faced by schools. The system development method used is Extreme Programming (XP) which has several stages, namely planning, designing, coding, testing and Software Increment. The results of this study are the creation of an information system that can provide several advantages as well as efficiency and effectiveness in processing information and managing value data up to the printing of student report cards.